Hungarian Monitoring, 27 July 1988 . [Magyar rádiófigyelő], 1988. július 27 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Khrushchev's secret speech - Situation in Karabakh Domestic Affairs: - Károly Grósz's closing statement on his American trip - Paper shortages - Workforce problems at Dorog Coalmine Economy: - Bond Council formed - Situation of animal husbandry Külpolitika - Hruscsov titkos beszéde - Karabahi helyzet Belpolitika - Grósz Károly amerikai látogatásának zárónyilatkozata - Papírhiány - Munkaerőgondok a Dorogi Szénbányában Gazdaság: - Megalakult az Értékpapírtanács - Az állattenyésztés helyzete